Miniature size branch line coupler - Omer Elhiwairis, Mohamed Yasir (2010)
The Branch Line Coupler (BLC) is one form of hybrid coupler. The structure consists of four quarter-wavelength transmission lines. The power to the input port is split into two equal output ports where the phase difference between the output ports is 90 degree. Due to its simple structure, the equal power split (3 dB) coupler is a very important element in RF front end system. In this project, miniature size Branch Line Coupler operating at 2.45 GHz will be designed and fabricated on FR4 Board and the performance analyzed by comparing the simulation and measurement results.